2005
DOI: 10.1021/jf0502000
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity of the Flavonoid Hesperidin in Chemical and Biological Systems

Abstract: The antioxidant hesperidin, a major flavonoid in sweet orange and lemon, was evaluated using chemical and biological systems. The chemical assay evaluates the hesperidin capacity to sequester 1,1-diphenyl-2-picrylhydrazyl (DPPH*). Biological studies were done using the eukaryotic cells of superoxide-dismutase proficient and deficient strains of Saccharomyces cerevisiae treated with hesperidin and the stressing agents hydrogen peroxide or paraquat (methylviologen; 1,1'-dimethyl-4,4'-bipyridinium dichloride). He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
166
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 270 publications
(174 citation statements)
references
References 30 publications
6
166
0
2
Order By: Relevance
“…Flavonoids are effectively used as supplemental agents to enhance the antioxidant status and boost the immune system (Kim et al, 2004;Wilmsen et al, 2005;. Free radicals increase as oxygen consumption increases, and are neutralized by a defense system including enzymatic and nonenzymatic antioxidants (Göktepe M et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Flavonoids are effectively used as supplemental agents to enhance the antioxidant status and boost the immune system (Kim et al, 2004;Wilmsen et al, 2005;. Free radicals increase as oxygen consumption increases, and are neutralized by a defense system including enzymatic and nonenzymatic antioxidants (Göktepe M et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Soares et al (2003) found that BHT and vitamin C were able to protect the yeast cells against damage caused by the stressing agents (apomorphine, paraquat and hydrogen peroxide). Other studies on phenolic compounds (quercetin, resveratrol, catechin and hesperidin) reported an increased oxidative stress resistance in yeast cells by scavenging free radicals (Belinha et al, 2007;Dani et al, 2008;Wilmsen et al, 2005). However, to the best of the authors' knowledge, there are no data on the ability of hydrophilic compounds of OJ to reduce the oxidative stress caused by H 2 O 2 in SC.…”
Section: Introductionmentioning
confidence: 94%
“…Previous studies have reported that different phenolic compounds (quercetin, resveratrol, catechin and hesperidin) and vitamin C are able to protect yeast cells against damage caused by different stressing agents (apomorphine, paraquat and hydrogen peroxide) (Belinha et al, 2007;Dani et al, 2008;Soares et al, 2003;Wilmsen et al, 2005). Also, phenolic compounds extracted from red wine, musts or skin extracts from dried grapes, showed the ability to rescue SC from the oxidative stress induced by H 2 O 2 , by either capturing free radicals or by activating endogenous defence system (Baroni et al, 2012;Ló pez de Lerma et al, 2013;Stefenon et al, 2010).…”
Section: Oj Serum Effect On the Survival Of Yeast Submitted To Oxidatmentioning
confidence: 99%
“…The results showed that blanching can increase the antioxidant activity as it increased flavanoid level. flavonoid is reported can act as antioxidant as it can take free radicals (Wilmsen et al, 2005).…”
Section: Total Flavonoid Content Of Beras Kencur Drinkmentioning
confidence: 99%